2022
DOI: 10.1111/idh.12620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brushing force on the abrasive dentin wear using slurries with different abrasivity values

Abstract: The aim of this study was to investigate the resulting abrasive dentin wear using abrasive slurries with different RDA values and applying increasing brushing forces. METHODS Fortyfive bovine incisors were randomly allocated in three groups (A, B, C, n = 15). One hundred and eighty dentin samples were prepared from these incisors and allocated to twelve groups (A1-A4, B1-B4, C1-C4; n = 15). The groups were subjected to a brushing cycle (120 strokes/min, 25 min) as follows: groups A1 to A4 with an abrasive slur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The abrasion values increase up to more than tenfold, depending on the bristle diameter, the number of bristles and the cleaned surface (number of bristles multiplied by the surface area of a single bristle) [ 4 ]. Furthermore, it has been shown that the bristle stiffness [ 23 ] and terminal shape [ 24 ] alone and in combination with different brushing forces [ 25 , 26 ] yield different abrasive wear results on dentine. It is, therefore, crucial to use only one toothbrush model consistently for all tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abrasion values increase up to more than tenfold, depending on the bristle diameter, the number of bristles and the cleaned surface (number of bristles multiplied by the surface area of a single bristle) [ 4 ]. Furthermore, it has been shown that the bristle stiffness [ 23 ] and terminal shape [ 24 ] alone and in combination with different brushing forces [ 25 , 26 ] yield different abrasive wear results on dentine. It is, therefore, crucial to use only one toothbrush model consistently for all tests.…”
Section: Resultsmentioning
confidence: 99%
“…Using different toothbrush models may compromise the comparability of results in different studies. Moreover, the abrasive wear on dentine changes for toothpaste slurries with different abrasivity depending on the used brushing force [ 26 ]. To avoid such effects and to ensure comparability of our brushing tests with RDA measurements, we chose a brushing force of 1.5 N, according to the standard [ 10 ], and kept it constant in all tests.…”
Section: Resultsmentioning
confidence: 99%
“…Wiegand et al 27 reported the mean brushing force applied with an electric toothbrush to be around 1 N (0.9 ± 0.1 N). Brushing at 1-N force was also reported to exhibit less abrasive damage to tooth structure compared to higher brushing forces 28 . At the same time, van der Weijden et al 29 reported that a regular lower brushing force (1.5 N) was more efficacious in removing plaque than a higher brushing force (3.5 N) using an electric toothbrush.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 , 22 , 23 , 24 ], or soft, as when biting the buccal and labial mucosa [ 23 ]. Abrasion has also been reported due to inadequate washing of vegetables containing soil [ 24 ] or due to inappropriate brushing techniques or abrasive toothpastes [ 20 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%